Pola Komunikasi Penyelesaian Konflik oleh Bidhumas Kepolisian Daerah (Polda) Sumatera Barat pada Kasus Perampokan oleh Oknum Polisi, Kematian Afif Maulana, dan Polisi Tembak Polisi Di Solok Selatan - Ernita Gusti; Rahmi Surya Dewi; Azwar . (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2025)
This study aims to analyze the conflict communication strategies implemented by the Public Relations Division (Bidhumas) of the West Sumatra Regional Police in responding to three critical cases that have significantly impacted the institution’s public image: the robbery committed by a police officer, the death of a teenager named Afif Maulana, and the “police shoots police” incident in South Solok. This research adopts a qualitative approach with a case study method and a constructivist paradigm. Data were collected through in-depth interviews, observation, and documentation. Data analysis was carried out using the interactive Pola of Miles and Huberman and thematic coding techniques with the assistance of NVivo 12 Plus software. The primary theoretical framework employed in this study is William L. Benoit’s Image Repair Theory. The findings reveal that the dominant communication strategies used include evasion of responsibility, reducing offensiveness, and corrective action, while mortification strategies (such as public apologies) tend to be avoided. The communication adopted by the institution is mostly one-way, normative, and defensive prioritizing image protection over efforts to restore public trust. The information conveyed to the public is limited and formal, creating a tension between the public’s demand for transparency and the institution’s attempt to maintain its reputation. Therefore, there is an urgent need for a more open, empathetic, and participatory communication pola in conflict resolution, particularly within law enforcement institutions, to foster long-term legitimacy and public confidence.